Development of Sharia-Based Goods and Services Procurement Theory in a Digital Context: An Explorative Study - Fahmi, Ismail; Ramlan, Ramlan; Perdana, Surya (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to develop a theory of Sharia-based procurement of goods and services in a digital context. Through an exploratory qualitative approach, this study explores the understanding of Sharia principles, the implementation of these principles in the context of digital procurement, as well as related challenges and strategies. The research results show that a good understanding of Sharia principles is a key to successful implementation. The implementation of Sharia principles in digital procurement can enhance transparency and efficiency, although there are some challenges to be overcome. This study indicates that further research, the development of tools and methods, as well as training and education are crucial strategies in developing the theory of Sharia-based procurement of goods and services in a digital context.